PENERBITAN SURAT KETERANGAN CATATAN KEPOLISIAN (SKCK) DALAM PERSPEKTIF PERLINDUNGAN HAK ASASI MANUSIA - Kadek Merry Herawati (Jurnal Ilmiah Raad Kertha, 2025)
A Police Clearance Certificate (SKCK) is a document issued by theIndonesian National Police (Polri) through its Intelligence and Security function toapplicants/members of the public to certify that the applicant has never been involvedin a crime or other offense. SKCKs are often required for job applications, public officecandidacy, educational registration, and other legal document processing. However,in practice, the SKCK issuance policy often poses challenges from a human rightsperspective, especially for former convicts or individuals with past legal convictions.Issues include how the issuance of Police Clearance Certificates is regulated and thesocial and legal impacts experienced by individuals who have difficulty obtainingPolice Clearance Certificates due to past criminal records.